The synthesis and characterisations of metallo-beta-amino alcohol complexes - Birtles, Samantha Lee (My University, 2011)
The ligands N,N‟-bis(2-hydroxycyclohexyl)-1,3-propanediamine (Cy2-tn), and 2,2‟-[(hydroxypropane-1,3-diyl)diimino]dicyclohexanol, (Cy2-Otn) and were synthesised and their solid state structures determined by X-ray diffraction experiments. Complexes were formed with the metal ions Pb(II), Cd(II), Ni(II), Cu(II) and Zn(II). The solid state structures of the Ni(II), Zn(II) and Cd(II) complex of Cy2-tn were determined by X-ray diffraction studies. The solid state structures of both the ligands, and their polymorphs, as well as the Cy2-tn/metal complexes mentioned, indicated the presence of hydrogen-hydrogen bonds between hydrogens on the cyclohexenyl rings and hydrogens on the propyl bridge. DFT calculations (X3LYP/6-31G(d,p))were performed on the Cy2-tn free ligand, the Cy2-tn Ni(II), Cu(II) and Zn(II) complexes, and on the ligand N,N‟-bis(2-hydroxycyclohexyl)-trans-cyclohexane-1,2- diamine (TCA) with Cu(II). The wavefunction files generated were used to study topolygical properties of the electron density using Bader‟s Quantum Theory of Atoms in Molecules (QTAIM). The resulting molecular graphs showed there were bond paths between hydrogen atoms on the cyclohexenyl rings in the TCA/Cu complex, but not in the Cy2-tn free ligand or the Cy2-tn/metal complexes. The DFT calculation also indicated that the L-M bonds are ionic with some covalent character, while the M-N bonds are suggested to be stronger, and more covalent in character than the M-O bonds. The slightly shared electron density character in the M-L bonds is seen by the charge on the metal ions being less than the formal 2+ charge. Potentiometric studies were performed on the Cy2-Otn ligand, and the complexes with Cu(II), Ni(II), Zn(II), Cd(II) and Pb(II). The protonation constant determination of the Cy2-Otn ligand resulted in pKa1 = 8.73 and a pKa2 = 7.31, however an impurity was present that was not seen in the characterisations. The Cy2-Otn/Cd and Pb(II) systems showed precipitation and were not analysed, while the Cy2-Otn/Zn system gave poor data. The Cy2-Otn/Cu system showed M(LH), ML and ML(OH) species present, whilst the Cy2-Otn/Ni system showed the presence of M(LH), ML, ML(OH), and ML(OH)2 species. The stability constants of the Cy2-Otn/metal ML species were compared to those previously reported for the Cy2-tn and Cy2-en ligands and their complexes with the metals studied.